Composite yarn and its manufacturing method

A two-step electrolytic plating process enhances the tensile strength and conductivity of carbon nanotube yarns by applying a controlled metal coating, addressing inefficiencies in existing methods and achieving superior performance for industrial applications.

JP7628692B2Active Publication Date: 2025-02-12SUGITA DENSEN CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2020070160
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-04-09
Publication Date
2025-02-12
Estimated Expiration
2040-04-09

AI Technical Summary

Technical Problem

Existing methods for electroplating carbon nanotube yarns are inefficient, time-consuming, and result in reduced tensile strength, making it difficult to achieve adequate electrical conductivity and adhesion of metal coatings, which are essential for industrial applications.

Method used

A method involving a two-step electrolytic plating process with controlled voltage application (0.1 to 3 V and 3 to 15 V) is used to coat carbon nanotube yarns with a metal layer, ensuring a thickness of 1 μm or more, and an internal metal area ratio of 5-70%, maintaining or enhancing tensile strength while improving conductivity.

Benefits of technology

The resulting composite yarn exhibits excellent tensile strength, high electrical conductivity, and effective adhesion of the metal coating, suitable for reducing wire harness and motor armature weight, with improved electrical properties and solderability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007628692000004
    Figure 0007628692000004
  • Figure 0007628692000005
    Figure 0007628692000005
  • Figure 0007628692000006
    Figure 0007628692000006
Patent Text Reader

Abstract

To provide a composite yarn which comprises carbon nanotubes, and which has a surface covered by a metal-plated layer and contains a metal also in its inside; and to provide a method for efficiently manufacturing the composite yarn by using a conventional industrial electrolytic plating method.SOLUTION: A composite yarn comprises: a twisted yarn comprising carbon nanotubes; and a metal-plated layer covering the surface of the twisted yarn. The thickness of the metal-plated layer is 1 μm or greater. The same metal as a metal covering the surface of the twisted yarn is precipitated inside the twisted yarn in an area ratio Sm / S (where Sm is the cross-section area of the metal portions present inside the twisted yarn comprising the carbon nanotubes, and S is the cross-section area of the twisted yarn portion comprising the carbon nanotubes) of 5-70% of the cross section of the twisted yarn. The breaking load of the composite yarn is 0.80 N or greater and is 80% or greater of the breaking load of the twisted yarn comprising the carbon nanotubes.SELECTED DRAWING: Figure 1(a)
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a composite yarn and a manufacturing method thereof, and more particularly to a composite yarn comprising a twisted yarn made of carbon nanotubes and a metal plating layer covering the surface of the twisted yarn, and a manufacturing method thereof. [Background technology]

[0002] 2. Description of the Related Art Conventionally, attempts have been made to plate carbon nanotubes (hereinafter sometimes abbreviated as CNT) as a technique for improving the electrical properties of the carbon nanotubes.

[0003] For example, Patent Document 1 (JP 2017-184105 A) discloses a conductive film body in which silver-plated CNT yarns are closely attached to the surface of a conductive film, but does not disclose a specific method for silver-plating the CNT yarns.

[0004] As a method for plating carbon fiber yarns having a carbon surface similar to that of CNT yarns, Patent Document 2 (JP Patent Publication No. 63-264968) discloses a method in which a bundle of carbon fibers (yarns) is subjected to a baking treatment at 300 to 800°C in an inert atmosphere and then electrolytic plating.

[0005] Patent Document 3 (JP Patent Publication 3-206173) discloses a method for producing metal-coated carbon fibers by attaching palladium colloid to the surface of a bundle of carbon fibers in an aqueous solution of a cationic surfactant and then carrying out electroless plating.

[0006] Patent Document 4 (JP 2009-220209) discloses a method for producing CNT fibers by immersing a CNT-oriented film in a metal plating solution and applying an electric current between the substrate of the CNT-oriented film and a winder while rotating the winder. It describes how the CNT bundles are continuously joined together by metal bridges from the metal plating solution generated by an electric field, thereby producing very long CNT fibers.

[0007] Patent Document 5 (JP 2010-70826 A) discloses a method for producing plated carbon fibers by performing supercritical treatment with a solution containing an organic complex metal as a pretreatment, followed by immersion in a plating solution for electroless plating.

[0008] Conventionally, electroless plating has been proposed because electrolytic metal plating on the CNT surface is not easy due to the fuzz on the CNT surface or the low electrical conductivity of the CNT yarn. However, with electroless plating, the metal coating easily peels off due to bending, etc., so a method for electrolytic plating has been desired.

[0009] As a method of electrolytic plating of yarn made of CNT, Non-Patent Document 1 (Kin Tae-seong et al., "Creation of Carbon Nanotube / Copper Composite Wiring by Electroplating and Evaluation of Allowable Current", Transactions of the Japan Society of Mechanical Engineers, December 14, 2017) discloses a method in which untwisted CNT yarn without a twist angle formed by a die is treated with an aqueous sodium hydroxide solution and an aqueous hydrochloric acid solution, then immersed in an aqueous copper sulfate solution for 48 hours, and electrolytic plating is performed at a low current density for a long time (5 hours). It is described that by pretreatment using an aqueous copper sulfate solution, the copper sulfate solution can be permeated into the inside of the CNT yarn, supplying metal nuclei for deposition inside the CNT yarn, and that by electrolytic plating at a low current density for a long time, metal deposition can be also precipitated inside the CNT yarn so that it is not biased toward the outer periphery. Non-Patent Document 1 describes that the current capacity is increased by precipitating metal inside the CNT yarn in this way.

[0010] However, the method described in Non-Patent Document 1 requires immersion in an aqueous copper sulfate solution for 48 hours and then electrolytic plating at a low current density for 5 hours in order to deposit metal inside the CNT yarn, which takes too long a processing time for industrial production. Therefore, there is a need to develop a method for producing composite yarn with metal deposited on the surface and inside of the yarn more efficiently in a shorter time.

[0011] Non-Patent Document 2 (J. Zou, et al., ACS Applied Materials & InterfaceS10, 8197-8204 (2018)) discloses a method for producing CNT / Cu composite yarns, in which electrolytic nickel plating is pretreated on CNT yarns (diameter 15°, twist angle 20°, strength 1.21±0.05 GPa) obtained by twisting two layers of vertically grown CNTs with a diameter of 4 nm, followed by continuous electrolytic copper plating. This pretreatment method is considered suitable for industrialization because it can be operated continuously with the desired copper plating process. Non-Patent Document 2 shows that no copper precipitation occurs inside the CNT / Cu composite yarns in energy dispersive X-ray spectroscopy (EDS) measurements of the cross section of the CNT / Cu composite yarns.

[0012] However, as described in Non-Patent Document 2, when electrolytic plating of nickel and copper is performed consecutively, the current densities of nickel and copper are different, making it difficult to precisely control the plating thickness. In order to precisely control the plating thickness, each plating must be performed separately, which ultimately increases the number of steps. In addition, because nickel plating is performed first, the deposition of copper into the inside of the CNT yarn, which would reduce the contact resistance inside the CNT yarn, is prevented.

[0013] In addition, in Non-Patent Document 2, because the electrical conductivity of CNT yarn is relatively high, electrolytic plating is performed directly on the CNT yarn, but the adhesion between the CNT surface and copper is insufficient and the desired performance is not achieved. Therefore, nickel electrolytic plating is performed as a pretreatment to coat the nickel surface with copper. However, as mentioned above, the nickel coating prevents the deposition of metal particles inside the CNT yarn, so the electrical conductivity depends mainly on the coated copper, and although this contributes to weight reduction as a result, it does not contribute to improving the electrical properties of the plated yarn as a whole. [Prior art documents] [Patent documents]

[0014] [Patent Document 1] JP 2017-184105 A [Patent Document 2] JP 63-264968 A [Patent Document 3] Japanese Patent Application Publication No. 3-206173 [Patent Document 4] JP 2009-220209 A [Patent Document 5] JP 2010-70826 A [Non-patent literature]

[0015] [Non-Patent Document 1] Kim Tae-seong et al., "Creation of Carbon Nanotube / Copper Composite Wiring by Electroplating and Evaluation of Allowable Current," Transactions of the Japan Society of Mechanical Engineers, 2017 / 12 / 14 [Non-Patent Document 2] J. Zou, et al., ACS Applied Materials & InterfaceS10, 8197-8204 (2018). Summary of the Invention [Problem to be solved by the invention]

[0016] Furthermore, as a result of further research by the present inventors, it was found that composite yarns (also simply referred to as composite yarns) that have been subjected to electrolytic plating treatment and manufactured by the method described in Non-Patent Document 1 have a lower breaking strength than CNT yarns before plating treatment. For example, when manufacturing a motor using these composite yarns, the composite yarns may break during the process of winding the composite yarns around a core, so the composite yarns are required to have a certain degree of tensile strength. Therefore, there is a need to develop CNT composite yarns that have been subjected to plating treatment and have sufficient tensile strength.

[0017] Therefore, a first object of the present invention is to provide a composite yarn consisting of carbon nanotubes whose surface is covered with a metal plating layer and which also contains metal inside, and a method for efficiently producing said composite yarn using a conventional industrial electrolytic plating method.

[0018] A second object of the present invention is to provide a composite yarn that can ensure sufficient tensile strength even after the plating treatment, and a method for producing the same. [Means for solving the problem]

[0019] As a result of intensive research in light of the above-mentioned object, the inventors have discovered that by subjecting a twisted yarn made of carbon nanotubes to a pretreatment of immersion in a plating solution without applying a voltage, followed by an electrolytic plating treatment (first plating treatment) with an applied voltage of 0.1 to 3 V, and then an electrolytic plating treatment (second plating treatment) with the applied voltage increased to 3 to 15 V, a plating layer can be formed on the surface of the twisted yarn made of carbon nanotubes with almost no decrease in tensile strength, and have arrived at the present invention.

[0020] That is, the composite yarn of the present invention is A composite yarn comprising a twisted yarn made of carbon nanotubes and a metal plating layer covering a surface of the twisted yarn, The thickness of the metal plating layer is 1 μm or more, a metal that is the same as the metal that coats the surface of the twisted yarn is precipitated inside the twisted yarn at an area ratio Sm / S of 5 to 70% of a cross section of the twisted yarn [where Sm is the cross-sectional area of ​​the metal portion present inside the twisted yarn made of carbon nanotubes, and S is the cross-sectional area of ​​the twisted yarn portion made of carbon nanotubes]; The composite yarn has a breaking load of 0.80 N or more, and is 80% or more of the breaking load of the twisted yarn made of carbon nanotubes.

[0021] The area ratio of the metal contained in the twisted yarn is S0, When the area ratio of the metal in the region surrounded by a circle having a radius of 1 / 2 of the radius of the twisted yarn from the center of the twisted yarn is S1, 0.1≦S1 / S0≦0.6 It is preferable that:

[0022] Preferably, the metal is copper.

[0023] Electrical conductivity is 1×10 6 S / m or more, and 1×10 7 It is more preferable that the value is S / m or more.

[0024] The breaking load of the composite yarn is preferably 90% or more of the breaking load of the twisted yarn made of carbon nanotubes not having a metal plating layer.

[0025] In the composite yarn, when the coated metal surface is soldered to a diameter of 1 to 10 mm and a tensile test is performed on the composite yarn, it is preferable that the soldered portion does not break before the unsoldered portion.

[0026] The twisted yarn made of carbon nanotubes preferably has a surface irregularity of 1 μm or less.

[0027] The twisted yarn made of carbon nanotubes preferably has 10 or less isolated bundles of carbon nanotubes per 10 μm of the twisted yarn length.

[0028] The twisted yarn made of carbon nanotubes preferably has a breaking strength of 700 MPa or more.

[0029] The twisted yarn made of the carbon nanotubes has a density of 0.2 to 2 g / cm 3 It is preferable that:

[0030] The area ratio Sm / S is preferably 15 to 60%.

[0031] In the composite yarn, the metal plating layer may be formed by laminating plating layers of two different metals, each of which may have a thickness of 1 μm or more.

[0032] The two different metals are preferably copper and tin from the surface side of the twisted yarn.

[0033] The method of the present invention for producing a composite yarn comprising a twisted yarn made of carbon nanotubes and a metal-plated layer coating the surface of the twisted yarn, the composite yarn further containing a metal, comprises the steps of: a plating solution immersion step of immersing the twisted yarn made of the carbon nanotubes in a plating solution for 0.1 to 360 minutes without applying a voltage, and an electrolytic plating step of electrolytically plating the twisted yarn that has been immersed in the plating solution; The electrolytic plating process is characterized by comprising a first plating process carried out at an applied voltage of 0.1 to 3 V, and a second plating process carried out after the first plating process at an applied voltage of 3 to 15 V.

[0034] In the method of the present invention, it is preferable to have, prior to the plating solution immersion treatment step, an organic solvent treatment step of immersing the twisted yarn in an organic solvent for 0.1 to 360 minutes, and a water treatment step of immersing the organic solvent-treated twisted yarn in water for 0.1 to 360 minutes.

[0035] In the method of the present invention, a metal is deposited inside the twisted yarn made of the carbon nanotubes in the first plating step, It is preferable that the surface of the twisted yarn made of the carbon nanotubes is coated with a metal in the second plating step.

[0036] In the method of the present invention, it is preferable to set the voltage and time of the first plating process so that the metal precipitated inside the twisted yarn made of carbon nanotubes has an area ratio Sm / S of 5 to 70% in the cross section of the composite yarn [wherein Sm is the cross-sectional area of ​​the metal portion present inside the twisted yarn made of carbon nanotubes, and S is the cross-sectional area of ​​the twisted yarn portion made of carbon nanotubes].

[0037] In the method of the present invention, it is preferable to set the voltage and time of the second plating step so as to coat the surface of the twisted yarn made of carbon nanotubes with a metal having a thickness of 1 μm or more.

[0038] In the method of the present invention, the breaking load after the first plating step is preferably 80% or more of the breaking load of the twisted yarn made of carbon nanotubes.

[0039] In the method of the present invention, the metal is preferably copper.

[0040] In the method of the present invention, the twisted yarn made of the carbon nanotubes is obtained by spinning a carbon nanotube array, The carbon nanotube array was subjected to two-dimensional Fourier transform processing of a range of [20 μm width in the direction parallel to the substrate (horizontal direction)] × [8 μm height direction from the substrate (vertical direction)] in an SEM photograph taken at a cross section parallel to the orientation direction, and a spatial frequency of 20 μm was obtained in the horizontal direction (0° direction) from the center of the obtained amplitude spectrum. -1 The amplitude is integrated up to f v , spatial frequency 20μm in the direction of 20° from the center -1 The amplitude is integrated up to f 20 Then, the formula: f 20 / f v ≦0.35 It is preferable that the following conditions are satisfied. Effect of the Invention

[0041] The composite yarn of the present invention is a CNT / metal composite yarn that contains precipitated particles of a metal such as copper inside the CNT twisted yarn and has the above-mentioned metal coating on the surface, and since the metal such as copper is formed in good adhesion to the CNT surface, the tensile strength is equal to or greater than that of hard copper, the adhesion between the CNT and the coating metal is excellent, and the electrical conductivity is excellent. The specific gravity of the composite yarn of the present invention is 55% or less compared to a copper electric wire of the same diameter, and furthermore, since the plated part can be subjected to conventional soldering processing, it is suitable for reducing the weight of wire harnesses and motor armatures. Furthermore, the copper-tin laminated electrolytically plated composite yarn obtained by the present invention makes it possible to treat tin, which is effective in shielding radiation, as a fiber. [Brief description of the drawings]

[0042] [Figure 1(a)]1 is an SEM photograph showing the surface of a composite yarn of the present invention (Example 1). [Figure 1(b)] 1 is an SEM photograph (secondary electron image) showing a cross section perpendicular to the longitudinal direction of a composite yarn of the present invention (Example 1). [Figure 1(c)] 1 is an SEM photograph (backscattered electron image) showing a cross section perpendicular to the longitudinal direction of a composite yarn of the present invention (Example 1). [Diagram 2] FIG. 1 is a cross-sectional view perpendicular to the longitudinal direction, which diagrammatically illustrates an example of a composite yarn of the present invention. [Figure 3(a)] 1 is an SEM photograph showing an example of a twisted yarn made of carbon nanotubes that constitutes the composite yarn of the present invention. [Figure 3(b)] 1 is an SEM photograph showing an example of a twisted yarn made of carbon nanotubes that constitutes the composite yarn of the present invention. [Figure 4] FIG. 2 is a schematic diagram showing a process for spinning carbon nanotubes from a carbon nanotube array to produce twisted yarn. [Figure 5(a)] 1 is a SEM photograph of a cross section of a carbon nanotube array taken in a direction parallel to the orientation direction, near the substrate. [Figure 5(b)] FIG. 6 is a diagram for explaining a method for determining f20 and fv from an amplitude spectrum obtained by performing a two-dimensional Fourier transform process on the SEM photograph of FIG. 5(a). [Figure 6(a)] 1 is a SEM photograph showing a twisted yarn made of carbon nanotubes used in Comparative Example 1. [Figure 6(b)] 1 is a SEM photograph showing a twisted yarn made of carbon nanotubes used in Comparative Example 1. [Figure 7(a)] 1 is an SEM photograph showing the surface of the composite yarn produced in Comparative Example 1. [Figure 7(b)] 1 is an SEM photograph (secondary electron image) showing a cross section perpendicular to the longitudinal direction of the composite yarn produced in Comparative Example 1. [Figure 7(c)] 1 is an SEM photograph (backscattered electron image) showing a cross section perpendicular to the longitudinal direction of the composite yarn produced in Comparative Example 1. [Figure 8(a)] 1 is an SEM photograph showing the surface of the composite yarn produced in Comparative Example 2. [Figure 8(b)]1 is an SEM photograph (secondary electron image) showing a cross section perpendicular to the longitudinal direction of the composite yarn produced in Comparative Example 2. [Figure 8(c)] 1 is an SEM photograph (backscattered electron image) showing a cross section perpendicular to the longitudinal direction of the composite yarn produced in Comparative Example 2. [Figure 9(a)] 1 is an SEM photograph showing the surface of the composite yarn produced in Comparative Example 3. [Figure 9(b)] 1 is an SEM photograph (secondary electron image) showing a cross section perpendicular to the longitudinal direction of the composite yarn produced in Comparative Example 3. [Figure 9(c)] 1 is an SEM photograph (backscattered electron image) showing a cross section perpendicular to the longitudinal direction of the composite yarn produced in Comparative Example 3. [Figure 10] 13 is a graph showing the relationship between displacement and load in a tensile test of the composite yarn produced in Comparative Example 3. [Figure 11] 13 is an SEM photograph showing the state in which the CNT twisted yarn and the copper coating on the surface were peeled off during a tensile test of the composite yarn produced in Comparative Example 3. [Figure 12(a)] 1 is an SEM photograph showing the surface of the composite yarn produced in Example 2. [Figure 12(b)] 1 is an SEM photograph (secondary electron image) showing a cross section perpendicular to the longitudinal direction of the composite yarn produced in Example 2. [Figure 12(c)] 1 is an SEM photograph (backscattered electron image) showing a cross section perpendicular to the longitudinal direction of the composite yarn produced in Example 2. [Figure 13] 1 is an SEM photograph showing the surface of the composite yarn produced in Comparative Example 4. [Figure 14(a)] 1 is an SEM photograph showing the surface of the composite yarn produced in Reference Example 1. [Figure 14(b)] 1 is an SEM photograph (secondary electron image) showing a cross section perpendicular to the longitudinal direction of the composite yarn produced in Reference Example 1. [Figure 14(c)] 1 is an SEM photograph (backscattered electron image) showing a cross section perpendicular to the longitudinal direction of the composite yarn produced in Reference Example 1. [Figure 15] FIG. 1 is a schematic diagram for explaining a method for performing a tensile test after performing a soldering process. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0043] [1] Composite yarn The composite yarn of the present invention comprises a twisted yarn made of carbon nanotubes and a metal plating layer covering the surface of the twisted yarn, The thickness of the metal plating layer is 1 μm or more, a metal that is the same as the metal that coats the surface of the twisted yarn is precipitated inside the twisted yarn at an area ratio Sm / S of 5 to 70% of a cross section of the twisted yarn [where Sm is the cross-sectional area of ​​the metal portion present inside the twisted yarn made of carbon nanotubes, and S is the cross-sectional area of ​​the twisted yarn portion made of carbon nanotubes]; The composite yarn has a breaking load of 0.80 N or more, and is 80% or more of the breaking load of the twisted yarn made of carbon nanotubes. In this specification, "carbon nanotube" may be abbreviated as "CNT".

[0044] The composite yarn of the present invention is obtained by electrolytic plating of a twisted yarn made of CNTs (hereinafter, also referred to as "CNT twisted yarn" or simply "twisted yarn"). FIG. 1(a) and FIG. 1(b) show SEM photographs of the surface and cross section perpendicular to the longitudinal direction of the composite yarn, respectively, and FIG. 2 shows a schematic diagram of a cross section perpendicular to the longitudinal direction of the composite yarn. As shown in these figures, the composite yarn 1 of the present invention has a metal plating layer 3 on the surface of the CNT twisted yarn 2, and also contains an internal metal 4 made of the same metal as the metal coating the surface inside the CNT twisted yarn 2. Hereinafter, the metal coating the surface of the CNT twisted yarn is also referred to as the "coating metal", and the metal contained inside the CNT twisted yarn is simply referred to as the "internal metal". In FIG. 1(b), the fibrous material surrounding the composite yarn is the resin used for embedding. The same applies to the following photographs.

[0045] (1) Metal plating layer The thickness of the metal plating layer that covers the surface of the CNT twisted yarn is 1 μm or more. By having a thickness of the metal plating layer of 1 μm or more, the composite yarn of the present invention has a thickness of 1×10 6It is possible to have a high electrical conductivity of 100 S / m or more. If the metal plating layer is too thick, it will have a weight similar to that of a metal wire, so the thickness is preferably 1 / 3 or less of the diameter and 10 μm or less.

[0046] The metal plating layer 3 that coats the surface of the CNT twisted yarn 2 may be composed of one type of metal (coating metal), or may be composed of two or more types of metals (coating metals) laminated together. When two or more types of coating metals are used, it is preferable that each metal has a thickness of 1 μm or more.

[0047] The metal for coating the surface of the CNT twisted yarn 2 is not particularly limited, and may be any transition metal or typical metal, but is preferably a metal selected from gold, silver, copper, and tin. Copper or tin is particularly preferred, and copper is most preferred. When two types of metals are used for coating, a combination of copper and tin is preferred. In this case, a configuration in which copper and tin are layered in this order from the surface side of the CNT twisted yarn 2 is preferred.

[0048] (2) Internal metal The composite yarn 1 of the present invention also contains inside the CNT twisted yarn 2 a metal (internal metal 4) that is the same as the coating metal that constitutes the metal plating layer 3. When there are two or more types of coating metals, it is preferable that the internal metal 4 is the same as the metal that is disposed on the inner side (the side in contact with the CNT twisted yarn) of the two types of coating metals.

[0049] The internal metal 4 is contained in the CNT twisted yarn 2, occupying 5 to 70% (area ratio) of the cross section. In other words, when the cross-sectional area of ​​the metal part present inside the CNT twisted yarn 2 is Sm and the cross-sectional area of ​​the CNT twisted yarn 2 part (part including the CNT twisted yarn 2 and the internal metal 4) is S, the area ratio Sm / S is 5 to 70%. As shown in FIG. 1(b), the metal (copper) present inside the CNT twisted yarn 2 is distributed in a scattered manner in fine particles when observed in cross section. Since the internal metal 4 occupies 5% (area ratio) or more of the cross section of the CNT twisted yarn 2, the electrical conductivity is more easily improved than in the case of only the metal coating (internal metal 4) on the outer periphery, and the adhesion between the internal metal 4 and the CNT twisted yarn 2 is improved. If the internal metal 4 is present in more than 70% (area ratio) of the cross section of the CNT twisted yarn 2, a decrease in breaking strength and a decrease in brittleness occur. The area of ​​the internal metal 4 in the cross section of the composite yarn 1 is preferably 10% or more, and more preferably 15% or more, of the cross-sectional area of ​​the CNT twisted yarn 2. The cross-sectional area of ​​the metal present inside the CNT twisted yarn 2 is preferably 65% ​​or less, and more preferably 60% or less, of the cross-sectional area of ​​the CNT twisted yarn.

[0050] Furthermore, it is preferable that more of the internal metal 4 is present near the surface of the CNT twisted yarn 2. By having the internal metal 4 near the surface, it becomes easier to connect with the metal plating layer 3 that covers the outer surface of the CNT twisted yarn 2, and the adhesion between the internal metal 4 and the CNT twisted yarn 2 is improved. When the area ratio of the internal metal 4 in the cross section of the CNT twisted yarn 2 is S0, and the area ratio of the internal metal 4 occupying the region from the center of the CNT twisted yarn 2 to 1 / 2 the radius of the CNT twisted yarn 2 is S1, then the formula: 0.1≦S1 / S0≦0.6 It is preferable that the following is satisfied. More preferably, 0.15≦S1 / S0≦0.55 When the internal metal 4 is uniformly present inside the CNT twisted yarn 2, the value of S1 / S0 is 1.

[0051] Here, the area ratio of the internal metal can be determined by determining the total area Sm of the internal metal parts and the cross-sectional area S of the twisted yarn part made of CNT (excluding the coated metal part but including the internal metal) by image processing or the like from a micrograph obtained by observing the cross section of the composite yarn with an SEM or the like, and then determining the area ratio Sm / S. Note that metals scattered in the SEM image can be identified, for example, by energy dispersive X-ray spectrometry.

[0052] (3) Porosity For example, as shown in Fig. 8(c), voids may exist inside the CNT twisted yarn. If voids exist inside the twisted yarn, when the composite yarn is used as a conductive wire, there is a possibility that the metal coating the surface of the composite yarn may melt due to heat generated by the current flowing through the surface of the composite yarn, so it is preferable that such voids are as few as possible. The void portion existing inside the twisted yarn is preferably 2% (area ratio) or less of the cross section of the twisted yarn, more preferably 1% (area ratio) or less, and most preferably 0% (area ratio).

[0053] (4) Carbon nanotube yarn 3(a) and 3(b) show an example of a twisted yarn (CNT twisted yarn) made of carbon nanotubes constituting the composite yarn of the present invention. The CNT twisted yarn can be obtained, for example, by preparing a carbon nanotube array made of a large number of carbon nanotubes vertically aligned on a substrate, drawing carbon nanotubes from the end of the carbon nanotube array, and twisting and spinning the short fibers of the drawn carbon nanotubes. Each carbon nanotube is preferably mainly made of a double-walled carbon nanotube and has an outer diameter of about 3 to 7 nm. The carbon nanotube array can be produced, for example, by a vapor phase synthesis method as described later.

[0054] The diameter of the CNT twisted yarn is not particularly limited, but is preferably about 10 to 100 μm. 3 S / m or more is preferable, and 10 4S / m or more is preferable, and 5×10 4 The tensile strength of the CNT twisted yarn is preferably 700 MPa or more. The density of the CNT twisted yarn is preferably 0.2 to 2 g / cm. 3 and preferably 0.5 to 1.3 g / cm 3 It is more preferable that:

[0055] The twist angle of the CNT twisted yarn (the angle of the short fibers with respect to the longitudinal direction of the twisted yarn) is preferably 5 to 50°. If the twist angle is less than 5°, the twist is insufficient and the voids become large, and if it exceeds 50°, the strength is poor.

[0056] The CNT twisted yarn preferably has a surface unevenness of 1 μm or less. The surface unevenness of the CNT twisted yarn is defined as the maximum value of the widthwise variation of the boundary between the CNT twisted yarn and the background in an image obtained by SEM observation. The widthwise variation is measured over at least 10 μm in the longitudinal direction of the CNT twisted yarn.

[0057] The number of isolated CNT bundles in the CNT twisted yarn is preferably 10 or less per 10 μm of yarn length. The number of isolated CNT bundles can be determined from images obtained by SEM observation.

[0058] It is preferable that the CNT twisted yarn has no peaks other than those caused by twisting in the Fourier transform spectrum of an SEM image.

[0059] (4) Properties of composite yarn From a practical standpoint, the composite yarn of the present invention preferably has a breaking load of 0.8 N or more, more preferably 0.90 N or more, even more preferably 0.95 N or more, and most preferably 1.0 N or more.

[0060] The composite yarn of the present invention has a breaking load of 80% or more compared to the CNT twisted yarn before electrolytic plating. In other words, when the CNT twisted yarn of the present invention is plated, the tensile strength does not decrease below 80%. Therefore, the composite yarn that has been electrolytically plated has a tensile strength equivalent to that of the CNT twisted yarn before the treatment, and is highly practical. The breaking load of the composite yarn is preferably 85% or more, more preferably 90% or more, and most preferably 95% or more of the breaking load of the CNT twisted yarn.

[0061] Furthermore, when the coated metal surface of the composite yarn of the present invention is soldered and a tensile test is performed, it is preferable that the soldered portion does not break before the non-soldered portion. For example, as shown in Fig. 15, one end of the composite yarn 101 is soldered 103 to a copper plate 102 (or a universal board), and the copper plate 102 and the other end of the composite yarn 101 are fixed to a tensile test mount 104 with adhesive 105, and a tensile test is performed to evaluate the adhesion between the copper plating layer and the CNT twisted yarn.

[0062] The composite yarn of the present invention has an electrical conductivity of 1×10 6 S / m or more is preferable, and 2×10 6 S / m or more is preferable, and 5×10 6 More preferably, it is 1×10 S / m or more. 7 It is most preferable that the thickness is equal to or larger than S / m.

[0063] [2] Manufacturing method of composite yarn A method for producing a composite yarn of the present invention, which comprises a twisted yarn made of carbon nanotubes and a metal plating layer covering the surface of the twisted yarn and further contains a metal inside the twisted yarn, comprises a plating solution immersion step of immersing the twisted yarn made of carbon nanotubes in a plating solution for 0.1 to 360 minutes without applying a voltage, and an electrolytic plating step of electrolytically plating the twisted yarn that has been immersed in the plating solution, The electrolytic plating process is characterized by comprising a first plating process carried out at an applied voltage of 0.1 to 3 V, and a second plating process carried out after the first plating process at an applied voltage of 3 to 15 V.

[0064] The method for producing a composite yarn of the present invention is characterized in that, prior to the plating solution immersion treatment step, it comprises an organic solvent treatment step of immersing the twisted yarn in an organic solvent for 0.1 to 360 minutes, and a water treatment step of immersing the organic solvent-treated twisted yarn in water for 0.1 to 360 minutes.

[0065] (1) Electrolytic plating The composite yarn of the present invention is produced by subjecting the CNT twisted yarn to first and second electrolytic plating. Here, the first plating process is carried out at an applied voltage of 0.1 to 3 V, and the second plating process is carried out at an applied voltage of 3 to 15 V. As a pretreatment for the electrolytic plating process, a plating solution immersion process is carried out to immerse the inside of the CNT twisted yarn in the plating solution. Furthermore, an organic solvent treatment and a water treatment may be carried out before the plating solution immersion process.

[0066] (a) Plating solution immersion process This is a treatment in which the CNT twisted yarn is immersed in a plating solution used in a subsequent electrolytic plating treatment without applying a voltage. The immersion time is preferably 0.1 to 360 minutes. By carrying out this plating solution immersion treatment, the plating solution can be permeated into the inside of the CNT twisted yarn, and the amount of metal precipitated inside the CNT twisted yarn in the subsequent electrolytic plating treatment can be increased. In order to further permeate the plating solution into the inside of the CNT twisted yarn, it is preferable to carry out an organic solvent treatment and a water treatment, which will be described later, before the plating solution immersion treatment. By carrying out an organic solvent treatment and a water treatment before the plating solution immersion treatment, a decrease in breaking strength after plating treatment can also be prevented.

[0067] (b) Organic solvent treatment process The CNT twisted yarn is immersed in the organic solvent for 0.1 to 360 minutes. The immersion time may be adjusted appropriately depending on the hydrophilicity or hydrophobicity of the CNT twisted yarn, its thickness, etc. As the organic solvent, it is preferable to use a water-soluble organic solvent, such as acetone, methyl alcohol, ethyl alcohol, isopropyl alcohol, acetonitrile, diethylene glycol, THF, DMF, DMSO, etc. In particular, acetone and alcohols are preferable.

[0068] (c) Water treatment process After the organic solvent treatment step, the CNT twisted yarn that has been treated with the organic solvent is immersed in water for 0.1 to 360 minutes. The immersion time can be adjusted appropriately depending on the hydrophilicity or hydrophobicity of the CNT twisted yarn, its thickness, etc. By carrying out the organic solvent treatment and water treatment in the previous stages, the plating solution can easily penetrate into the inside of the CNT twisted yarn, which can promote the deposition of metal inside the CNT twisted yarn in the electrolytic plating treatment step.

[0069] (d) Electrolytic plating process The electrolytic plating process includes a first plating process carried out at an applied voltage of 0.1 to 3 V, and a second plating process carried out after the first plating process at an applied voltage of 3 to 15 V. In the first plating process, metal is deposited mainly inside the CNT twisted yarn, and in the second plating process, a metal plating layer is coated mainly on the surface of the CNT twisted yarn.

[0070] In the first plating process, if the applied voltage is less than 0.1 V, electrolytic plating will not occur, and if it exceeds 3 V, the plating speed will be too fast and a metal plating layer will form on the surface of the CNT twist before the metal precipitates inside the CNT twist, preventing metal from precipitated inside the CNT twist.

[0071] The voltage and time of the first plating step are preferably set so that the metal deposited inside the CNT twisted yarn has an area ratio Sm / S of 5 to 70% in the cross section of the composite yarn [where Sm is the cross-sectional area of ​​the metal part present inside the CNT twisted yarn, and S is the cross-sectional area of ​​the CNT twisted yarn part]. The treatment time is preferably in the range of 1 to 90 minutes, more preferably in the range of 2 to 60 minutes. The treatment temperature (temperature of the plating solution) is preferably in the range of 10 to 40°C.

[0072] After the metal is deposited in the interior of the CNT twisted yarn at a desired area ratio, the applied voltage is increased to coat the surface of the CNT twisted yarn with metal (second plating process). The second plating process is carried out at an applied voltage of 3 to 15 V. If the applied voltage in the second plating process is less than 3 V, it is difficult to coat the surface of the CNT twisted yarn with metal, and if it exceeds 15 V, the plating speed is too fast, making it difficult to control the thickness of the metal coating layer. The applied voltage in the second plating process is preferably 3.5 to 12 V, and more preferably 4.0 to 10 V.

[0073] The voltage and time of the second plating process are preferably set so as to coat the surface of the CNT strand with a metal having a desired thickness of 1 μm or more. The preferred treatment time is in the range of 1 to 20 minutes. The treatment temperature (temperature of the plating solution) is preferably in the range of 10 to 40° C.

[0074] As the electrolytic plating solution, a commercially available plating bath can be used. For example, as the plating solution for electrolytic copper plating, a commercially available industrial plating solution (e.g., electrolytic copper plating solution manufactured by Kiyokawa Plating Industry Co., Ltd., copper plating solution manufactured by Marui Plating Industry Co., Ltd.) can be used.

[0075] In the electrolytic plating process of the present invention, the metal to be electrolytically plated is preferably copper. After copper has been electrolytically plated by the method of the present invention, it may be further coated with a metal such as tin.

[0076] (2) Manufacturing twisted yarn made of carbon nanotubes A twisted yarn made of carbon nanotubes (CNT twisted yarn) can be obtained by producing a CNT array made of a large number of CNTs vertically oriented on a substrate by a vapor phase synthesis method, drawing out short CNT fibers from the ends of the array, and twisting and spinning the short CNT fibers. The CNT twisted yarn is preferably produced by the method described in, for example, JP 2019-59663 A.

[0077] From the viewpoint of spinnability, the CNT array preferably has an average CNT length of 80 to 350 μm, more preferably 110 to 200 μm, and a bulk density of 100 to 200 mg / cm. 3 and preferably 120 to 180 mg / cm 3 The size of the substrate on which the CNT array is formed is not particularly limited, but from the viewpoint of spinning, it is preferable that the width is about 2 cm and the length is about 2 to 4 cm. It is preferable that the CNTs of the CNT array are mainly double-walled CNTs and have an outer diameter of about 3 to 7 nm.

[0078] (a) Fabrication of carbon nanotube arrays CNT arrays are manufactured by supplying a carbon source gas to a substrate with a reaction catalyst formed on its surface in a hydrogen gas atmosphere, reacting at a specified temperature for a specified time to form a large number of vertically aligned CNTs on the substrate, and then holding the resulting mixture in a non-oxidizing atmosphere for a specified time and then cooling it. The CNT arrays obtained by this method have high spinnability, and high-quality spun yarns can be obtained from the CNT arrays with high reproducibility.

[0079] FIG. 4 shows a schematic diagram of a process for spinning CNTs from a CNT array to produce a CNT twisted yarn. The CNT array 10 obtained by the above-mentioned method is composed of a large number of carbon nanotubes 12 formed vertically aligned on a substrate 11, as shown in FIG. 4(a). When a 3-5 mm portion is split parallel to one side of the substrate 11 and the smaller substrate piece 11a is pulled apart horizontally, the short fibers of the carbon nanotubes 12 are continuously aligned between the larger substrate piece 11b and the smaller substrate piece 11a to form a plurality of fibers 12a (see FIG. 4(c)). The plurality of fibers 12a thus drawn are twisted by, for example, rotating the substrate piece 11b around the axis of the drawing direction to produce a twisted yarn 2 composed of the carbon nanotubes 12 (see FIG. 4(d)). The CNT twisted yarn 2 thus obtained is wound around a bobbin 13 or the like.

[0080] In the SEM photograph taken at a cross section parallel to the orientation direction, the CNT array was subjected to two-dimensional Fourier transform processing within a range of [20 μm width in the direction parallel to the substrate (horizontal direction)] × [8 μm height direction from the substrate (vertical direction)], and a spatial frequency of 20 μm was obtained from the center of the obtained amplitude spectrum in the horizontal direction (0° direction). -1 The amplitude is integrated up to f v , spatial frequency 20μm in the direction of 20° from the center -1 The amplitude is integrated up to f 20 Then, the formula: f 20 / f v ≦0.35 When the CNT array satisfies the above formula, the CNTs have high regularity in the horizontal direction on the CNT array, and thus the spinnability is particularly excellent.

[0081] where f 20 and f vThe position of the amplitude spectrum to be integrated to obtain is explained with reference to Figure 5. Figure 5(a) is an SEM photograph of the carbon nanotube array taken at a cross section parallel to the orientation direction near the substrate, and Figure 5(b) is an amplitude spectrum obtained by two-dimensional Fourier transform processing of the range of [20 μm width in the direction parallel to the substrate (horizontal direction)] × [8 μm height direction from the substrate (vertical direction)] in the SEM photograph of Figure 5(a). -1 The line segment A is the distance from the center to the center, and the spatial frequency is 20 μm -1 The line segment B shows the amplitude on the line segment A. v The integrated amplitude on line segment B is f 20 f 20 / f v The smaller the value of f, the higher the horizontal periodicity in the original image of the cross section of the CNT array (the CNTs are neatly arranged in the vertical direction). 20 / f v The larger the value of , the lower the horizontal periodicity, indicating that the CNT arrangement is more disordered.

[0082] Example 1 (1) Preparation of CNT yarn A thin SiO2 film (approximately 30 nm) was formed on the surface of a silicon plate (a 6-inch silicon wafer (100) manufactured by SUMCO cut into a size of 20 mm x 40 mm) by thermal oxidation, and then an Al2O3 film (approximately 15 nm) was formed by sputtering. After the Al2O3 film was formed on the silicon plate, it was washed with an organic solvent and treated with ozone, and then an Fe thin film (1.7-2.0 nm) was formed by electron beam deposition.

[0083] The silicon plate on which the Fe thin film was formed was placed in a CVD apparatus (manufactured by U-TECH Co., Ltd.) and heated in a vacuum (10 Pa or less) at 150°C for 10 minutes to remove any air, moisture, etc. remaining on the substrate. Hydrogen gas was then supplied to the CVD apparatus, and the temperature was raised to 400°C in a hydrogen gas atmosphere and held at 400°C for 5 minutes to reduce the oxide film on the surface of the Fe thin film and form Fe fine particles.

[0084] The supply of acetylene gas was then started at 400°C, and the temperature was raised to 800°C over 1 minute 45 seconds, and maintained for 10 minutes to synthesize carbon nanotubes. The mixture ratio of acetylene gas to hydrogen gas was 100:692 (acetylene gas with a mole fraction of 0.126, total pressure: 800 Pa). After maintaining at 800°C for 10 minutes, the supply of acetylene gas was stopped to stop the synthesis, and heat treatment was performed at 800°C for 10 minutes in a hydrogen gas atmosphere (total pressure: 800 Pa). After the heat treatment, the supply of hydrogen gas was stopped, and the temperature was lowered to room temperature in a vacuum over 30 minutes, and a carbon nanotube array in which carbon nanotubes were formed on the substrate was obtained.

[0085] The obtained carbon nanotube array 10 is composed of a large number of carbon nanotubes 12 vertically aligned on a substrate 11, as shown in FIG. 4(a). A 3-5 mm portion of one side of the substrate 11 is split parallel to the side, as shown in FIG. 4(b), and the smaller substrate piece 11a is pulled away horizontally, as shown in FIG. 4(c). The substrate piece 11b is rotated around the axis of the drawing direction to twist a plurality of fibers 12a (fibers in which short fibers of carbon nanotubes 12 are continuously aligned) formed between the larger substrate piece 11b and the smaller substrate piece 11a, to produce a twisted yarn 2 composed of carbon nanotubes 12 (see FIG. 4(d)). The CNT twisted yarn 2 thus obtained is wound around a bobbin 13 or the like.

[0086] SEM images of this CNT yarn are shown in Figures 3(a) and 3(b). This CNT yarn has a diameter of 40 μm, a breaking load of 1.16 N, and a conductivity of 6.07 × 10 4 S / m, density is about 0.5 g / cm 3 It was.

[0087] The unevenness of the surface of the CNT twisted yarn was defined as the maximum value of the widthwise variation of the boundary between the CNT twisted yarn and the background area measured in the longitudinal direction for at least 10 μm from the images obtained by SEM observation. The unevenness of the surface of the obtained CNT twisted yarn was 0.3 to 0.5 μm.

[0088] The number of isolated bundles was determined by measuring the number of isolated bundles per 10 μm of the CNT twisted yarn from images obtained by SEM observation. The number of isolated bundles in the obtained CNT twisted yarn was 3 / 10 μm.

[0089] f 20 / f v is a parameter that indicates the degree of orientation of the CNT array used to produce the CNT twisted yarn. In an SEM photograph taken of a cross section of the CNT array parallel to the orientation direction, a range of [20 μm width in the direction parallel to the substrate (horizontal)] × [8 μm height direction from the substrate (vertical)] is subjected to two-dimensional Fourier transform, and a spatial frequency of 20 μm is obtained in the horizontal direction (0° direction) from the center of the obtained amplitude spectrum. -1 The amplitude is integrated up to f v , spatial frequency 20μm in the direction of 20° from the center -1 The amplitude is integrated up to f 20 Then, f 20 / f v The f of the obtained CNT yarn is 20 / f v The value was 0.29.

[0090] (2) Electrolytic plating Electrolytic plating was performed using an electrolytic copper plating solution (undiluted) (Kiyokawa Plating Co., Ltd., H2SO4: 18 mass%, CuSO4·5H2O: 10 mass%, H2O: 72 mass%), a copper plate washed with acetone and then pure water was used as the anode, and the prepared CNT twisted yarn was used as the cathode, and a voltage was applied using a DC stabilized power supply at room temperature (25°C). As a pretreatment, the CNT twisted yarn was immersed in acetone, pure water, and the plating solution, in that order, for 10 minutes. Note that the pretreatment of immersion in the plating solution was performed without applying voltage. Electrolytic plating was performed by applying a voltage of 0.5 V for 45 minutes (first plating process) and then applying a voltage of 4.5 V for 5 minutes (second plating process). In the first plating process, copper was precipitated mainly inside the CNT twisted yarn, and in the second plating process, a copper plating layer was formed mainly on the surface of the CNT twisted yarn. The current values ​​in the first plating step and the second plating step were about 0.2 mA and 2 mA, respectively.

[0091] The diameter of the obtained composite yarn was 66 μm, the diameter of the CNT twisted yarn portion was 60 μm, and the thickness of the metal plating layer was 3 μm. The diameter of the CNT twisted yarn before the electrolytic plating process (40 μm) increased to 60 μm after the electrolytic plating process, which is believed to be due to the deposition of copper inside the CNT twisted yarn. The electrical conductivity of this composite yarn was 2.64 × 10 6 The breaking load was 1.09 N. This breaking load value was 94% of the breaking load of the CNT twisted yarn before the electrolytic plating treatment.

[0092] Figures 1(a), 1(b), and 1(c) show SEM images of the obtained composite yarn. Figure 1(a) is a photograph observing the appearance, Figure 1(b) is a secondary electron image of the cross section, and Figure 1(c) is a backscattered electron image of the cross section. In Figure 1(b), the white parts are Cu. From these results, it was confirmed that copper particles were precipitated inside the composite yarn, and further that the surface of the CNT twisted yarn was covered with copper.

[0093] Comparative Example 1 The CNT twisted yarn shown in Figures 6(a) and 6(b) was produced using Hamamatsu Carbonix NTA05 [CNT array with 30-40 layers (diameter 30 nm)]. This CNT twisted yarn has a diameter of 40 μm, a breaking load of 0.4 N, and a density of 0.1 g / cm. 3 The surface roughness is 2-3 μm, the number of isolated bundles is 15 / 10 μm or more, and f 20 / f v The value was 0.48.

[0094] This CNT twisted yarn was subjected to electrolytic plating in the same manner as in Example 1 to obtain the composite yarn shown in Figures 7(a), 7(b), and 7(c). The current values ​​in the first and second plating steps were approximately 0.3 mA and 2 mA, respectively.

[0095] The diameter of the obtained composite yarn was 51 μm, the diameter of the CNT twisted yarn portion was 45 μm, and the thickness of the metal plating layer was 3 μm. The electrical conductivity of this composite yarn was 1.87 × 10 7The fracture toughness was 0.77 N and the breaking load was 192% of the breaking load of the CNT twisted yarn before electrolytic plating. The fracture surface showed that the CNTs had been pulled out of each other, unlike ordinary CNT yarns. This sample was easily broken by bending.

[0096] The composite yarn of Comparative Example 1 has a high area ratio Sm / S of 85%, meaning that a relatively large amount of metal precipitated in the CNT twisted yarn portion, and a relatively large S1 / S0 value, meaning that metal precipitated deep inside the twisted CNT yarn (see Table 2). The reason that a large amount of metal precipitated and that metal precipitated deep inside the twisted CNT yarn is thought to be because the density of the CNT twisted yarn before electrolytic plating treatment was low, meaning that there were many voids and the plating solution was easily absorbed. For this reason, this composite yarn had a low tensile strength with a breaking load of 0.77 N.

[0097] Comparative Example 2 The CNT twisted yarn produced in Example 1 (diameter: 40 μm, breaking load: 1.16 N, electrical conductivity: 6.07 × 10 4 S / m) was used, and electrolytic plating was performed in the same manner as in Example 1, except that the second plating step was not performed, to obtain a composite yarn in which copper was precipitated inside the CNT twisted yarn. Figures 8(a), 8(b), and 8(c) show SEM photographs of the obtained composite yarn.

[0098] The diameter of the obtained composite yarn was 46 μm, the diameter of the CNT twisted yarn portion was 46 μm, and the thickness of the metal plating layer was almost 0 μm. The electrical conductivity of this composite yarn was 9.97 × 10 4 The breaking load was 1.02 N. This breaking load value was 88% of the breaking load of the CNT twisted yarn before the electrolytic plating treatment.

[0099] Comparative Example 3 The CNT twisted yarn produced in Example 1 (diameter: 40 μm, breaking load: 1.16 N, electrical conductivity: 6.07 × 10 4A composite yarn was obtained by electrolytic plating in the same manner as in Example 1, except that the first plating step was not performed using a 1.0 S / m electrode. Figures 9(a), 9(b) and 9(c) show SEM photographs of the obtained composite yarn. The electrical conductivity of this composite yarn was 3.50 × 10 6 S / m.

[0100] A tensile test was conducted on the obtained composite yarn. The relationship between the displacement and the load is shown in Figure 10. As shown in Figure 11, the tensile test showed that the CNT twisted yarn and the copper coating on its surface peeled off before the composite yarn broke. As is clear from Figures 9(b) and 9(c), copper was not precipitated inside the CNT twisted yarn, and a gap was generated between the CNT twisted yarn and the copper coating. It is believed that this is why the CNT twisted yarn and the copper coating on its surface peeled off during the tensile test. In other words, it can be seen that when only the second plating process is carried out without carrying out the first plating process, almost no metal (copper) is precipitated inside the CNT twisted yarn.

[0101] Example 2 The CNT twisted yarn produced in Example 1 (diameter: 40 μm, breaking load: 1.16 N, electrical conductivity: 6.07 × 10 4 Using a 1000 cc copper foil (1.0 S / m), electrolytic plating was carried out in the same manner as in Example 1, except that pretreatment involved immersion in acetone and water, but only immersion in the plating solution (10 minutes), to obtain a composite yarn with copper precipitated inside the CNT twisted yarn. SEM photographs of the obtained composite yarn are shown in Figures 12(a), 12(b), and 12(c). The electrical conductivity of this composite yarn was 7.30 × 10 6 The breaking load was 0.95 N. This breaking load value was 82% of the breaking load of the CNT twisted yarn before the electrolytic plating treatment.

[0102] Comparative Example 4 The CNT twisted yarn produced in Example 1 (diameter: 40 μm, breaking load: 1.16 N, electrical conductivity: 6.07 × 10 4The electrolytic plating process was carried out in the same manner as in Example 2, except that the second plating step was not carried out, using a copper alloy (S / m) and a composite yarn in which copper was precipitated inside the CNT twisted yarn was obtained. Figure 13 shows an SEM photograph of the obtained composite yarn. The electrical conductivity of this composite yarn was 1.14 × 10 5 The breaking load was 0.77 N. This breaking load value was 66% of the breaking load of the CNT twisted yarn before the electrolytic plating treatment.

[0103] This composite yarn had almost no copper plating on the surface of the CNT twisted yarn, similar to Comparative Example 2. The results of Comparative Examples 2 and 4 show that when only the first plating step is performed without the second plating step, almost no copper plating is applied to the surface of the CNT twisted yarn. In other words, it is believed that the plating of the surface is mainly performed by the second plating step.

[0104] Table 1 shows the diameters of the CNT twisted yarns used in Example 1, Example 2, and Comparative Examples 1 to 4, and the plating steps.

[0105] [Table 1] Note 1: CNT yarn made using Hamamatsu Carbonix NTA05

[0106] The composite yarn diameter, plating layer thickness, internal metal area ratios Sm / S, S1 / S0, and porosity obtained from cross-sectional SEM photographs of the composite yarns produced in Example 1, Example 2, and Comparative Examples 1 to 4 are shown in Table 2. Table 3 also shows the electrical conductivity, breaking load, and ratio of the breaking load of the composite yarn after plating to the breaking load of the CNT twisted yarn before plating.

[0107] [Table 2] Note 1: No cross-sectional observation was performed.

[0108] [Table 3] Note 1: The ratio of the breaking load of the composite yarn after plating to the breaking load of the CNT twisted yarn before plating. Note 2: The CNT strand and the coated Cu peeled off, making it impossible to measure.

[0109] Reference example 1 The CNT twisted yarn produced in Example 1 (diameter: 40 μm, breaking load: 1.16 N, electrical conductivity: 6.07 × 10 4 S / m) was used to perform electrolytic plating in the same manner as in Example 1 to obtain a composite yarn in which copper was precipitated inside the CNT twisted yarn, and then the obtained composite yarn was further electrolytically plated with tin to produce a CNT / copper / tin composite yarn in which a tin plating layer was formed on the surface of the copper plating layer. For the electrolytic plating of tin, Mekki Kobo Tin Plating Solution (semi-gloss) manufactured by Marui Plating Co., Ltd. was used as the plating solution, and the treatment was performed at 3.0 V for 1 minute. The current value at this time was 1.2 mA.

[0110] The diameter of the obtained composite yarn was 57 μm, the diameter of the CNT twisted yarn portion was 51 μm, the thickness of the copper plating layer was 2 μm, the thickness of the tin plating layer was 1 μm, the area ratio Sm / S was 48%, S1 / S0 was 0.49, and the porosity was 0.9%. The electrical conductivity of this composite yarn was 7.04 × 10 6 The breaking load was 0.80 N. This breaking load value was 69% of the breaking load of the CNT twisted yarn before the electrolytic plating treatment. [Explanation of symbols]

[0111] 1. Composite yarn 2. CNT yarn 3. Metal plating layer 4...internal metal 10. Carbon nanotube array 11... Substrate 11a... Board piece 11b... Board piece 12. Carbon nanotubes 12a Multiple Fibers 13. Bobbin 101...Composite yarn 102...Copper plate 103 Soldering 104 Tensile test sheet 105...Adhesive

Claims

1. A method for producing a composite yarn comprising a twisted yarn made of carbon nanotubes and a metal-plated layer coating the surface of the twisted yarn, the method comprising the steps of: a plating solution immersion step of immersing the twisted yarn made of the carbon nanotubes in a plating solution for 0.1 to 360 minutes without applying a voltage, and an electrolytic plating step of electrolytically plating the twisted yarn that has been immersed in the plating solution; The method for producing a composite yarn, wherein the electrolytic plating process comprises a first plating process carried out at an applied voltage of 0.1 to 3 V, and a second plating process carried out after the first plating process at an applied voltage of 3 to 15 V.

2. In the method for producing a composite yarn according to claim 1, A method for producing a composite yarn, comprising, prior to the plating solution immersion treatment step, an organic solvent treatment step of immersing the twisted yarn in an organic solvent for 0.1 to 360 minutes, and a water treatment step of immersing the organic solvent-treated twisted yarn in water for 0.1 to 360 minutes.

3. In the method for producing a composite yarn according to claim 1 or 2, In the first plating step, a metal is deposited inside the twisted yarn made of the carbon nanotubes, A method for producing a composite yarn, characterized in that in the second plating process, a metal is coated on the surface of the twisted yarn made of the carbon nanotubes.

4. In the method for producing a composite yarn according to claim 3, A method for producing a composite yarn, characterized in that the voltage and time of the first plating process are set so that the metal precipitated inside the twisted yarn made of carbon nanotubes has an area ratio Sm / S of 5 to 70% in the cross section of the composite yarn [wherein Sm is the cross-sectional area of ​​the metal portion present inside the twisted yarn made of carbon nanotubes, and S is the cross-sectional area of ​​the twisted yarn portion made of carbon nanotubes].

5. In the method for producing a composite yarn according to claim 3 or 4, A method for producing a composite yarn, characterized in that the voltage and time of the second plating process are set so as to coat the surface of the twisted yarn made of carbon nanotubes with a metal thickness of 1 μm or more.

6. In the method for producing a composite yarn according to any one of claims 1 to 5, A method for producing a composite yarn, characterized in that the metal is copper.

7. In the method for producing a composite yarn according to any one of claims 1 to 6, the twisted yarn made of carbon nanotubes is obtained by spinning a carbon nanotube array; The carbon nanotube array was subjected to two-dimensional Fourier transform processing in a range of [20 μm width in the direction parallel to the substrate (horizontal direction)] × [8 μm height direction from the substrate (vertical direction)] in an SEM photograph taken at a cross section parallel to the orientation direction, and a spatial frequency of 20 μm was obtained in the horizontal direction (0° direction) from the center of the obtained amplitude spectrum. -1 The amplitude is integrated up to f v , spatial frequency 20μm in the direction of 20° from the center -1 The amplitude is integrated up to f 20 When this is done, the formula: f 20 / f v ≦0.35 A method for producing a composite metal, comprising the steps of:

8. A composite yarn comprising a twisted yarn made of carbon nanotubes and a metal plating layer covering a surface of the twisted yarn, The thickness of the metal plating layer is 1 μm or more, A composite yarn, characterized in that a metal that is the same as the metal that coats the surface of the twisted yarn is precipitated inside the twisted yarn at an area ratio Sm / S of 5 to 70% of the cross section of the twisted yarn, where Sm is the cross-sectional area of ​​the metal portion present inside the twisted yarn made of carbon nanotubes, and S is the cross-sectional area of ​​the twisted yarn portion made of carbon nanotubes.

9. The composite yarn according to claim 8, The area ratio of the metal contained in the twisted yarn is S0, When the area ratio of the metal in the region surrounded by a circle having a radius of 1 / 2 of the radius of the twisted yarn from the center of the twisted yarn is S1, 0.1≦S1 / S0≦0.6 A composite yarn comprising:

10. The composite yarn according to claim 8 or 9, A composite yarn characterized in that the metal is copper.

11. The composite yarn according to any one of claims 8 to 10, Electrical conductivity is 1×10 6 A composite yarn characterized by a thickness of S / m or more.

12. The composite yarn according to any one of claims 8 to 11, Electrical conductivity is 1×10 7 A composite yarn characterized by a thickness of S / m or more.

13. The composite yarn according to any one of claims 8 to 12, The twisted yarn made of the carbon nanotubes is a composite yarn characterized in that the surface irregularities are 1 μm or less.

14. The composite yarn according to any one of claims 8 to 13, The carbon nanotube twisted yarn has a density of 0.2 to 2 g / cm 3 A composite yarn comprising:

15. The composite yarn according to any one of claims 8 to 14, A composite yarn characterized in that the area ratio Sm / S is 15 to 60%.

16. The composite yarn according to any one of claims 8 to 15, The composite yarn is characterized in that the metal plating layer is formed by laminating plating layers of two different metals, and each plating layer has a thickness of 1 μm or more.

17. 17. The composite yarn according to claim 16, wherein the two different metals are copper and tin from the surface side of the twisted yarn.

Citation Information

Patent Citations

  • Metal plating of carbon fiber bundle

    JP1988264968A

  • Production of carbon yarn coated with metal

    JP1991206173A

  • Method for manufacturing carbon nanotube fiber and apparatus for manufacturing carbon nanotube fiber

    JP2009220209A

  • Manufacturing method of conductive fiber

    JP2010070826A

  • Conductive film-like body, antenna device, and communication apparatus

    JP2017184105A